Management of pericarditis - Ombretta Para; Eleonora Blasi; Martina Finocchi; Tiziana Ciarambino; Chiara Florenzi; Davide Carrara; Elisabetta Benetti; Mariella Frualdo; Antonio Brucato (Italian Journal of Medicine, 2019)
Pericarditis is an inflammatory syndrome involving pericardium, which is a double-walled sac consisting of two leaves, a serous visceral layer in contact with the myocardium (pericardium) and a parietal fibrous one, delimiting a cavity (pericardial cavity) containing pericardial fluid. Pericarditis may occur isolated or as a manifestation of a systemic disorder. Diagnosis and correct management of pericarditis can be difficult and its natural history is often characterized by a lot of relapses. Treatment of acute pericarditis should target the underlying etiology. The diagnosis is based on characteristic clinical findings, electrocardiogram, and echocardiography. The goals of treatment are relief of pain, resolution of inflammation (and, if present, pericardial effusion), and prevention of recurrence. Despite a significant impairment of the quality of life, pericarditis usually has good long-term outcomes.